Sarcopenia is a prognostic outcome marker in children with high‐risk hepatoblastoma. Issue 5 (12th January 2021) - Ritz, Annika; Kolorz, Julian; Hubertus, Jochen; Ley‐Zaporozhan, Julia; von Schweinitz, Dietrich; Koletzko, Sibylle; Häberle, Beate; Schmid, Irene; Kappler, Roland; Berger, Michael; Lurz, Eberhard
Abstract: Background: Children with hepatoblastoma (HB) are at risk of sarcopenia due to immobility, chemotherapy, and malnutrition. We hypothesized that children with HB have a low preoperative total psoas muscle area (tPMA), reflecting sarcopenia, which negatively impacts outcome. Procedure: Retrospective study of children (1‐10 years) with hepatoblastoma treated at a large university children's hospital from 2009 to 2018. tPMA was measured as the sum of the right and left psoas muscle area (PMA) at intervertebral disc levels L3‐4 and L4‐5. z ‐Scores were calculated using age‐ and gender‐specific reference values and were compared to anthropometric measurements, clinical variables, and outcomes. Sarcopenia was defined as a tPMA z ‐score below −2. Results: Thirty‐three children were included. Mean tPMA z ‐score was −2.18 ± 1.08, and 52% were sarcopenic. A poor correlation between tPMA and weight was seen ( r = 0.35; confidence interval [CI] 0.01, 0.62; P = .045), and most children had weights within the normal range (mean z ‐score −0.55 ± 1.39). All children categorized as high risk with relapse (n = 5/12) were sarcopenic before surgery. Relapse was significantly higher in the high‐risk sarcopenic group compared to the nonsarcopenic group ( P = .008). The change in tPMA z ‐score 1‐4 months after surgery did not improve in patients with relapse, but did improve in 75% of children without relapse. Conclusions: The majority of children with HB were sarcopenic prior to surgery. Especially in children with high‐risk hepatoblastoma, sarcopenia is an additional risk factor for relapse. Large multicenter studies are needed to confirm these preliminary results.